The effect of competence and discipline on employee performance at PT Lautan Belawan Jaya - Hoki, Leony; Purba, Yessica Sardina; Florenza, Viona (Priviet Social Sciences Journal, 2024)
This research employs a quantitative descriptive approach. The sampling technique utilized non-probability total sampling, incorporating questionnaires, interviews, and observations with a population of 30 employees. Data analysis techniques in- clude tests for validity, reliability, multicollinearity, normality,  heteroscedasticity, t, F, multiple linear regression, and the coefficient of determination (R2). The results reveal that the coefficient of determination (Adjusted R Square) is 0.302, indicating that competence (X1) and discipline (X2) explain 30.2% of employee performance (Y), while the remaining 69.8% is influenced by other variables outside this research, such as work stress, work environment, and communication. Partial test results show that competency influences employee performance with a t-value of 3.253, which is greater than the t-table value of 1.99773, and a significance value  of 0.000, which  is less than 0.05. Discipline also influences employee performance with a t-value of 4.297, which is greater than the t-table value  of 1.99773, and a significance value  of 0.000, which is less than 0.05. The F-value of 15.259 is greater than the F-table value of 3.98, indicating that the competency (X1) and discipline (X2) variables simultaneously influence employee performance (Y) at PT Lautan Belawan Jaya.